2008 IEEE Conference on Computer Vision and Pattern Recognition 2008
DOI: 10.1109/cvpr.2008.4587835
|View full text |Cite
|
Sign up to set email alerts
|

Non-refractive modulators for encoding and capturing scene appearance and depth

Abstract: We analyze the modulation of a light field via non-refracting attenuators. In the most general case, any desired modulation can be achieved with attenuators having four degrees of freedom in ray-space. We motivate the discussion with a universal 4D ray modulator (ray-filter) which can attenuate the intensity of each ray independently. We describe operating of such a fantasy rayfilter in the context of altering the 4D light field incident on a 2D camera sensor. Ray-filters are difficult to realize in practice b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…In particular, spatial patterns are chosen such that the different slices of the plenoptic function are encoded into different frequency bands. In computer graphics, this optical heterodyne approach has so far been used for capturing light fields [32,31], occluder information [14], and high dynamic range color photographs [34]. Spatially encoded light fields were recently analyzed in Fourier space and it was demonstrated that Fourier reconstruction algorithms apply as well [10].…”
Section: Background and Related Workmentioning
confidence: 99%
“…In particular, spatial patterns are chosen such that the different slices of the plenoptic function are encoded into different frequency bands. In computer graphics, this optical heterodyne approach has so far been used for capturing light fields [32,31], occluder information [14], and high dynamic range color photographs [34]. Spatially encoded light fields were recently analyzed in Fourier space and it was demonstrated that Fourier reconstruction algorithms apply as well [10].…”
Section: Background and Related Workmentioning
confidence: 99%
“…A modern elaboration of this approach where the sensor and a micro-lens array are combined to form an incamera light-field imaging system is the Hand-Held Plenoptic Camera [17]. Alternatively, sensor masks [22,21] or a light pipe [15] can be arranged such that in-camera lightfields can be recorded. Other methods use external arrays of mirrors instead of lenses [7], or external lens arrays [4].…”
Section: Related Workmentioning
confidence: 99%
“…Representative work includes: Veeraraghavan et al [6,72], who designed mask enhanced cameras to heterodyne the band-limited light fields in the frequency domain for refocusing; Ng [32], who analyzed the 4D light field captured by a lenslet based camera [12] in the Fourier domain and selected its specific slice trajectory for refocusing; and Georgiev et al [73], who analyzed the light field cameras under a unified framework in the frequency domain. Other researchers performed demosaicing [74] or computed 3D occluders and cast shadows [75] in the frequency domain.…”
Section: Computational Reconstructionmentioning
confidence: 99%